The Mythology of Capital - v. Hayek, F. A. (Quarterly Journal of Economics, 1936)
I. Professor Knight's argument, 199.— II. On some current misconceptions: 1. The investment periods and technological progress, 204; 2. They refer to factors, not products, 205; 3. The aggregate of such periods cannot be reduced to an average, nor is measurability essential, 206; 4. The periods refer always to the future, never to the past, 208; 5. The concept does not depend on a distinction between original and produced means of production, 209; 6. Nor is it only the original means of production whose investment periods can be changed, 209.— III. Professor Knight's criticism based on a misunderstanding, 210.— IV. His own position prevents him from giving any explanation of how the limitation of capital restricts the increase of output, 213.— V. An erroneous assertion following from his fundamental position: the value of capital goods when interest disappears, 222.— VI. Problems of capital and "perfect foresight, " 225.